Efektifitas Pembelajaran Menggunakan Media E-Learning (Cisco Webex) - Diani Syahfitri; Muhammad Aufa Muis (STAIN Bengkalis, 2020)
Education 4.0 is a form of education that integrates cyber technology both physically and not into learning or in other words as a phenomenon of digital penetration in the educational world. This model education is present to respond to the needs of the fourth industrial revolution where people and machines are aligned to get solutions. Solve problems and of course discover the possibilities of new innovations. The presence of this technology becomes an alternative model of learning and utilization. E-learning becomes a formal and informal learning solution through Cisco Webex applications making learning without space and time limits. Through e-learning, access to various learning resources, be it content or human. E-learning provides an opportunity for students to take control of their success. Webex tools for meeting online. This tool is a tool issued by CISCO, where Webex is currently the most popular media and widely used by people ranging from small, medium to large companies to conduct regular meetings between employees online. Therefore, the use of webex applications in a learning process as e-learning is reliable for every educator in maximizing and achieving learning goals.